(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Persea americana has been identified to possess antihypertensive properties, but the mechanisms of these properties remain unclear. This study was thus designed to elucidate the mechanisms of anti-hypertensive activity of the extract and fractions of fresh leaf of Persea americana on hypertension induced in rats. Methods: Crude methanol leaf extract of P. americana was partitioned into n-butanol, dichloromethane, chloroform, hexane and ethyl acetate. The ethyl acetate fraction was further purified through column chromatography. Doses of the extract and column fraction were tested for contraction on rat isolated thoracic rings and for in vitro angiotensin converting enzyme inhibitory activities. The test doses were further evaluated for anti-hypertensive activities on noradrenaline- and L-NAME-induced hypertension as well as atherogenic index in hyperlipidemic rats. Effects were compared with control values via one-way analysis of variance using GraphPad® version 8.0 software Results: P. americana leaf methanol extract and ethyl acetate column fraction 3 reduced the contractile effect of noradrenaline significantly (p < 0.001) in the isolated thoracic aortic rings through intact endothelium-mediated mechanism(s). The test doses also exhibited in vitro angiotensin converting enzyme inhibitory activities similar to that of captopril. Additionally, ethyl acetate column fraction 3 also reduced the hypertensive effect of L-NAME- induced hypertension by 23% Conclusion: Persea americana methanol leaf extract and ethyl acetate column fraction 3 exhibited significant reductions in all the tested parameters of L-NAME and noradrenaline-induced hypertension most probably through inhibition of vascular alpha adrenoceptors, angiotensin converting enzyme and amelioration of dyslipidemia.